PEMBELAJARAN HAM DI SEKOLAH DAN TRANSFORMASI PEMBELAJARAN PPKN MELALUI PROBLEM-BASED LEARNING UNTUK MENINGKATKAN KESADARAN HAM SISWA - Rachmatul Fitria Nur; Hana Hanifah Balqis; Adelweiss Afghani Zahra; Zaenul Slam (STKIP Subang, 2026)
This study aims to analyze the effectiveness of implementing the Problem-Based Learning (PBL) model in increasing students' Human Rights (HAM) awareness in Pancasila and Citizenship Education (PPKn) subjects. The research method used is library research with a descriptive qualitative approach. Data collection was carried out through searching reputable scientific literature, including journal articles, textbooks, and related regulatory documents. The results of the analysis indicate that conventional Civics learning which is theoretical contributes to low social sensitivity and high rates of bullying in schools. The PBL model is proven effective in overcoming these obstacles by exposing students to dilemmas and real case studies of human rights violations. Through the PBL syntax, students are encouraged to think critically, discuss in groups, and formulate solutions to human rights issues. This study concludes that the implementation of PBL in Civics education not only improves students' cognitive understanding, but also reconstructs civic disposition based on values of tolerance and respect for human rights.